ANALISIS USAHATANI SAYURAN HIDROPONIK SAWI (Brassica rapa L.) DI KECAMATAN TANJUNG REDEB KABUPATEN BERAU (Analysis of Hydroponic Vegetable Farming of Mustard (Brassica rapa L.) in Tanjung Redeb Subregency, Berau Regency) - FAHRUL RAHMAN; MARIYAH MARIYAH; ARSYADANI SABILAL HAQ (JURNAL AGRIBISNIS DAN KOMUNIKASI PERTANIAN (Journal of Agribusiness and Agricultural Communication), 2021)
Hydroponic provides solutions for cultivated agriculture on narrow land. It begins to be done by people of Tanjung Redeb that live in urban area to utilize land for mustard hydroponic farming. Mustard is chosen because it has a lot of enthusiasts and has high selling price. This research aimed to know the production cost, revenue, profit, and feasibility of hidroponic vegetable farming of mustard. This research was conducted in Tanjung Redeb Subregency, Berau Regency. This research took a sample of 15 respondents who actively work on hydroponic farming. The research results showed that the production cost incurred for hidroponic vegetable farming of mustard in a year with a frequency of 10 harvests was IDR116,990,975.00 or an average of IDR7,799,397.00 respondent-1. Hydroponic vegetable farming of mustard is profitable with value R/C ratio of 6.60 with the average revenue and profit in a year per respondent were IDR51,483,333.00 and IDR43,683,936.00, respectively.